2018
DOI: 10.1002/pssb.201800126
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Slow Decay of Yellow Luminescence in Be‐Doped GaN and Its Identification

Abstract: The extremely slowly decaying yellow luminescence band around 2.08 eV in GaN:Be:O is studied by continuous-wave and time-resolved photoluminescence, as well as photoluminescence excitation spectroscopy and absorption. The lifetime obtained for this process is around 2.2 s and is thermally quenched for temperatures between 250 and 400 K. From the photoluminescence excitation measurements, two major pumping thresholds at around 2.7 and 3.1 eV can be identified. We discuss the origin of the Be-related 2.08 eV tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 79 publications
(116 reference statements)
3
13
0
Order By: Relevance
“…[ 40,41 ] These facts indicate that the transition level of the defect responsible for the YL Be2 band is not lower than ≈0.8 eV above the valence band. Moreover, from analysis of time‐resolved PL and PL excitation spectra, Lamprecht et al [ 40 ] concluded that the broad YL Be2 band consists of three PL bands with maxima at 1.88, 2.08, and 2.12 eV, one of which (2.12 eV) is likely caused by the C N acceptor. The 2.08 eV component was attributed to the Be Ga O N complex.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 40,41 ] These facts indicate that the transition level of the defect responsible for the YL Be2 band is not lower than ≈0.8 eV above the valence band. Moreover, from analysis of time‐resolved PL and PL excitation spectra, Lamprecht et al [ 40 ] concluded that the broad YL Be2 band consists of three PL bands with maxima at 1.88, 2.08, and 2.12 eV, one of which (2.12 eV) is likely caused by the C N acceptor. The 2.08 eV component was attributed to the Be Ga O N complex.…”
Section: Discussionmentioning
confidence: 99%
“…The decay of the YL Be2 intensity after a pulsed excitation is extremely slow (up to several seconds at low temperatures). [40] Most importantly, the quenching of the YL Be2 band begins at temperatures well above room temperature, and the YL Be2 band could be excited with photon energies as low as 2.75 eV. [40,41] These facts indicate that the transition level of the defect responsible for the YL Be2 band is not lower than %0.8 eV above the valence band.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 A similar yellow band in bulk GaN with high concentrations of Be and O is attributed to the BeGaON complex. 40 This yellow band is quenched only at T > 500 K, 41 which indicates that the related defect level is located at about 0.8 eV above the VBM. The third mechanism of PL quenching is the Seitz-Mott mechanism.…”
Section: Quenching Of Photoluminescencementioning
confidence: 99%